2023
DOI: 10.3390/jcm12051831
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, a Regulator of Androgen Levels, Is Not Correlated to PSA Serum Levels in a Cohort of the Middle Italy Region Participating to a Prostate Cancer Screening Campaign

Abstract: Prostate cancer (PCa) is the most common non-cutaneous malignancy in men worldwide, and it represents the fifth leading cause of death. It has long been recognized that dietary habits can impact prostate health and improve the benefits of traditional medical care. The activity of novel agents on prostate health is routinely assessed by measuring changes in serum prostate-specific antigen (PSA) levels. Recent studies hypothesized that vitamin D supplementation reduces circulating androgen levels and PSA secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The overall incidence rate stands at 31 cases per 100,000 males across all age groups, while the lifetime cumulative risk is estimated at 3.9%. Notably, the prevalence of PCa among men aged 75 and above exceeds one in four individuals ( 37 , 38 ). While the majority of cases are indolent and do not result in death, a substantial number of cases present with intermediate- or high-risk localized, locally advanced, or metastatic cancer despite treatment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence rate stands at 31 cases per 100,000 males across all age groups, while the lifetime cumulative risk is estimated at 3.9%. Notably, the prevalence of PCa among men aged 75 and above exceeds one in four individuals ( 37 , 38 ). While the majority of cases are indolent and do not result in death, a substantial number of cases present with intermediate- or high-risk localized, locally advanced, or metastatic cancer despite treatment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can also explain why studies have observed lower concentrations of vitamin D in men with lower urinary tract symptoms (LUTS) ( 71 ). The impact of vitamin D is well described in certain tumors; however, the findings regarding the role of vitamin D in prostate cancer and serum PSA levels are contradictory and lack consistency ( 72 , 73 ). Moreover, there has a possible relationship between vitamin D and urinary tract infection (UTI), erectile dysfunction (ED), and the male reproductive system ( 74 – 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another important topic is whether vitamin D can be used as a surrogate marker for prostate cancer screening that potentially will help predict the presence or progression of the disease. A recent study found an absence of correlation between the serum vitamin D concentration levels and prostate cancer risk[ 17 ]. There are still too few large-scale, well-conducted studies to confirm the absence of correlation.…”
Section: Vitamind D and Prostate Cancermentioning
confidence: 99%